Gene expression profiling of Epstein–Barr virus‐positive diffuse large B‐cell lymphoma of the elderly reveals alterations of characteristic oncogenetic pathways. Issue 5 (9th April 2014) - Kato, Harumi; Karube, Kennosuke; Yamamoto, Kazuhito; Takizawa, Jun; Tsuzuki, Shinobu; Yatabe, Yasushi; Kanda, Teru; Katayama, Miyuki; Ozawa, Yukiyasu; Ishitsuka, Kenji; Okamoto, Masataka; Kinoshita, Tomohiro; et al.
<x xml:space="preserve">Abstract</x> Epstein–Barr virus (EBV)‐positive diffuse large B‐cell lymphoma (DLBCL) of the elderly (EBV[+]DLBCL‐E) is classified as a subtype of DLBCL. Until now, its molecular pathogenesis has remained unknown. To identify pathways characteristic of EBV(+)DLBCL‐E, gene expression profiling of five EBV(+)DLBCL‐E and seven EBV‐negative DLBCL (EBV[−]DLBCL) cases was undertaken using human oligonucleotide microarray analysis. Gene set enrichment analysis and gene ontology analysis showed that gene sets of the Janus kinase‐signal transducer and activator of transcription (JAK‐STAT) and nuclear factor kappa B (NF‐κB) pathways were enriched in EBV(+)DLBCL‐E cases. To confirm the results of the expression profiles, in vitro analysis was performed. Expression profiling analysis showed that high activation of the JAK‐STAT and NF‐κB pathways was induced by EBV infection into DLBCL cell lines. Activation of the NF‐κB pathway was confirmed in EBV‐infected cell lines using an electrophoretic mobility shift assay. Western blot analysis revealed an increased protein expression level of phosphorylated signal transducer and activator of transcription 3 (STAT3) in an EBV‐infected cell line. Protein expression of phosphorylated STAT3 was frequently observed in lymphoma cells of EBV(+)DLBCL‐E clinical samples using immunohistochemistry (EBV[+]DLBCL‐E: 80.0% [n = 20/25] versus EBV[−]DLBCL: 38.9% [n = 14/36]; P = 0.001). The results of the present study suggest that activation of the JAK‐STAT and NF‐κB pathways was characteristic of EBV(+)DLBCL‐E, which may reflect the nature of EBV‐positive tumor cells. Targeting these pathways as therapies might improve clinical outcomes of EBV(+)DLBCL‐E.